2022
DOI: 10.1155/2022/7346460
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA MMP2-AS1 Contributes to Progression of Renal Cell Carcinoma by Modulating miR-34c-5p/MMP2 Axis

Abstract: Renal cell carcinoma (RCC) serves as a prevalent malignancy of urinary system and presents severe mortality and increasing incidence. Long noncoding RNAs (lncRNAs) have demonstrated critical roles in RCC development. Here, we were interested in the function of MMP2-AS1 during RCC progression. We observed that MP2-AS1 localized in both nucleus and cytoplasm of RCC cells using fluorescent in situ hybridization (FISH). The cell viability, proliferation, invasion, and migration of RCC cells were reduced by the dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…Among the MMPs, MMP2 is capable of cleaving ECM molecules and signal transduction molecules, promoting the spread of tumors. It has been reported that MMP2 is involved in the metastasis of various cancers, such as breast cancer, 39 renal cell carcinoma, 40 esophageal squamous cell carcinoma, 41 and lung cancer 42 . In gastric cancer, MMP2 overexpression might be a predictive factor for poor prognosis 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Among the MMPs, MMP2 is capable of cleaving ECM molecules and signal transduction molecules, promoting the spread of tumors. It has been reported that MMP2 is involved in the metastasis of various cancers, such as breast cancer, 39 renal cell carcinoma, 40 esophageal squamous cell carcinoma, 41 and lung cancer 42 . In gastric cancer, MMP2 overexpression might be a predictive factor for poor prognosis 43 .…”
Section: Discussionmentioning
confidence: 99%
“…MiRNA-34c-5p is a member of the miRNA-34 family, miRNA-34 family can inhibit tumor progression by promoting apoptosis and blocking the cell cycle [ 30 ]. And miRNA-34c-5p has been shown to exert oncogenic effects in renal cell carcinoma, oral squamous cell carcinoma and other tumors by targeting MMP2 and TRIM29 to inhibit cell proliferation, invasive and migration [ 31 , 32 ]. Thus, finding the target genes of miRNA-34c-5p in GC could help us to investigate the mechanism by which miRNA-34c-5p inhibits GC progression.…”
Section: Discussionmentioning
confidence: 99%
“…As a potential treatment target, MMP2-AS1 affects the proliferation, invasion and migration of renal cell carcinoma (RCC) cells by controlling the miR-34c-5p/MMP2 axis to promote the development of RCC. ( Fan et al, 2022 ). Besides, a study constructed and verified a prognostic risk model of targeting autophagy-related gene (ATG) which contains MMP2-AS1 in NSCLC patients and found that this gene was closely involved in immune modulation in TME.…”
Section: Discussionmentioning
confidence: 99%